Internalisasi Nilai-Nilai Pancasila dalam Membentuk Moral Pancasila Generasi Milenial - Inayah Junika Zahira (JURNAL PENCAKAR (Pendidikan Pancasila dan Kewarganegaraan), 2026)
Pancasila is the way of life of the Indonesian people which is used as the norms that apply in Indonesia. This means that all applicable regulations must be based on Pancasila, including morals. The millennial generation must have good character and morals to create a quality next generation. The millennial generation needs to equip themselves with morals based on Pancasila values in their daily lives, to maintain the identity of the Indonesian nation.